2009
DOI: 10.1111/j.1346-8138.2009.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life for Korean patients with vitiligo: Skindex‐29 and its correlation with clinical profiles

Abstract: Vitiligo considerably influences the psychological well-being of patients. Disease-induced disfigurement can cause patients to experience a high level of stigmatization, which can lead to psychosocial stresses and negative impacts on quality of life (QOL). This study aims to ascertain the QOL of vitiligo patients compared to patients with other mild skin disorders. We also attempt to study which clinical features of vitiligo are closely related to the patient's QOL. One hundred and thirty-three vitiligo patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 18 publications
1
26
0
1
Order By: Relevance
“…We found that the emotional condition of patients with VD and VE was negatively affected. In some of the studies that evaluated the emotional subscales of the Skindex-29, mean emotional scores are reported as 10.7 for striae,8 12.3 for ectodermal dysplasia,17 29.518 and 30.719 for vitiligo, 40 for idiopathic pruritus,20 and 48 for discoid lupus erythematosus (DLE) 21. The mean emotional scores in the VD group were found to be close to those previously reported for DLE.…”
Section: Discussionsupporting
confidence: 76%
“…We found that the emotional condition of patients with VD and VE was negatively affected. In some of the studies that evaluated the emotional subscales of the Skindex-29, mean emotional scores are reported as 10.7 for striae,8 12.3 for ectodermal dysplasia,17 29.518 and 30.719 for vitiligo, 40 for idiopathic pruritus,20 and 48 for discoid lupus erythematosus (DLE) 21. The mean emotional scores in the VD group were found to be close to those previously reported for DLE.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, 82% of the patients chose the VLQI as the scale by which they could express themselves and which reflected the problems they faced better. Kim et al [11] also observed that the quality of life correlates with patient's disease severity, but not with the doctor's disease severity assessment. As Kostopoulou et al [12] were studying the factors determining the psychological effects of vitiligo, they found that the disease severity perceived by the patients and the personalities of the patients were the determinants of quality of life.…”
Section: Discussionmentioning
confidence: 98%
“…Psychological aspects of skin diseases, including atopic dermatitis (AD), psoriasis, urticaria, alopecia areata and vitiligo, have been widely investigated. Understanding the psychological aspects of skin diseases and implementing psychological treatment approaches have been increasingly emphasized1-5.…”
Section: Introductionmentioning
confidence: 99%
“…Vitiligo is characterized by hypopigmented macules of the skin or mucosa, with no accompanying subjective symptoms other than the skin lesion itself. Although vitiligo does not cause serious physical morbidity, patients with the disease may experience various degrees of psychological stress and altered QoL1,2.…”
Section: Introductionmentioning
confidence: 99%